Multiclass least-squares support vector machines for analog modulation classification - Sengur, Abdulkadir (Pergamon-Elsevier Science Ltd, 2009)
This study introduces the usage of multiclass least-squares support vector machines (MC-LS-SVM) for classification purposes of the analog modulated communication signals. Fulfilled study uses our previous papers where ANN and clustering methods were used as classifiers and several key features which were extracted from the instantaneous properties of the intercepted signal for characterizing the modulation types. k-fold cross-validation test, classification accuracy and confusion matrix methods are used for calculating the performance of the MC-LS-SVM classifier. Moreover, the performance of the MC-LS-SVM is compared with our previous Studies where ANN and Clustering efforts for modulation classification were investigated. According to the computer simulations, 100% correct classification rate was obtained when 10-fold cross-validation test method was used. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Modulation recognition; Feature extraction; Least-squares support vector machines